A graph-based machine learning framework identifies critical properties of FVIII that lead to hemophilia A - Ferreira, Marcos V.; Nogueira, Tatiane; Rios, Ricardo A.; Lopes, Tiago J. S. (Frontiers in Bioinformatics, 2023)
Blood coagulation is an essential process to cease bleeding in humans and other species. This mechanism is characterized by a molecular cascade of more than a dozen components activated after an injury to a blood vessel. In this process, the coagulation factor VIII (FVIII) is a master regulator, enhancing the activity of other components by thousands of times. In this sense, it is unsurprising that even single amino acid substitutions result in hemophilia A (HA) – a disease marked by uncontrolled bleeding and that leaves patients at permanent risk of hemorrhagic complications. Despite recent advances in the diagnosis and treatment of HA, the precise role of each residue of the FVIII protein remains unclear. In this study, we developed a graph-based machine learning framework that explores in detail the network formed by the residues of the FVIII protein, where each residue is a node, and two nodes are connected if they are in close proximity on the FVIII 3D structure. Finally, in an effort to advance the development of novel recombinant therapeutic FVIII proteins, we adapted our framework to predict the activity and expression of more than 300 in vitro alanine mutations, once more observing a modest agreement between the in silico and the in vitro results. Together, the results derived from this study demonstrate how graph-based classifiers can leverage the diagnostic and treatment of a rare disease.